Observations on some aberrant Australian Anatidae - Johnsgard, Paul A (Wildfowl, 1965)
Field observations on the Pink-eared Duck, Freckled Duck, Musk Duck and Blue-billed Duck generally confirm earlier conclusions regarding the affinities of these birds. The Pink-eared Duck’s vocalisations and displays suggest that it is an aberrant dabbling duck having surprising behavioral similarities to the typical shovelers that are probably the result of evolutionary convergence. The Freckled Duck exhibits a curious mixture of swan or goose-like anatomical and behavioral features that must be weighed against a duck-like bodily form. These conflicting and unusual features of the species suggest that it should be given tribal status in the subfamily Anserinae, or at the very least should be removed from the dabbling duck tribe, with which it shares almost no features. Observations on flight, sound production and sexual behaviour of the Musk Duck, and on molts and vocalisations in the Blue-billed Duck are included.